The Accuracy of Sanitary Pad of Nitrazine Test in the Diagnosis of Premature Rupture of Membranes - Haseli 1*, Arezoo; Afshar 2, Bahare (Shahroud Journal of Medical Sciences, 2019)
Background: Sanitary Pad of Nitrazine Test (SPONT) is one of the newest method to diagnosis premature rupture of membranes (PROM) that doesn't need women attending hospital and applying speculum. The aim of this study was to assess the performance of SPONT versus standard clinical assessment.Methods: A prospective diagnostic accuracy study, 140 pregnant women with symptoms of PROM in 22-42 weeks of gestation were involved. The accuracy of SPONT in the diagnosis of PROM was compared with Nitrazine, Fern and Pooling tests that were performed at the same time.Results: The sensitivity, specificity, positive predictive value, and negative predictive value of SPONT, routine Nitrazine, Fern and Pooling tests were 93.2%, 85.7%, 97.3%, 69.2%; 94.1%, 90.5%, 98.2% 73.1%; 80.1%, 95.2%, 98.9%, 46.5%; and 68.1%, 95.2%, 98.9% 46.5%, respectively. The sensitivity of SPONT was the same as routine Nitrazine test (P.V=0.811). SPONT has higher sensitivity than Fern test (P.V=0.008) and Pooling test (P.V<0.001). The accuracy of the applied tests was 92.1%, 93.6%, 82.8% and 72.8% respectively for SPONT, Nitrazine, Fern and Pooling tests. There wasn't significant difference between accuracy of SPONT and standard clinical assessment (92.1% vs. 89.3%).Conclusions: The accuracy of SPONT was the same as routine Nitrazine test in PROM diagnosis that pregnant women can use it if they do not have immediate access to health centers.